Voltammetric and spectrometric determination of antioxidant capacity of selected wines - Lino, F. M. A. (2014)
Considering the presence of phenolics in grapes and wines, as well as their importance for health promoting properties, the DPPH (1,1-diphenyl-2-picrylhidrazine) assay and a novel electroanalytical approach (differential pulse voltammetry – DPV) for analysis have been performed in order to compare the antioxidant activity of different grape beverages. A total of fifty-two wine samples from different regions around the world were analyzed. The antioxidant activity of the different wines analyzed was expresses as the amount of wine required to produce 50% of decolorization of DPPH relative to the blank control (EC50) and as an electrochemical index (EI), obtained by summing the ratios between peak current and peak potential values. Red wines presented higher antioxidant capacity than rose and white ones or red juices, evidencing the influence of the overall process of fabrication in phenolic extraction from the skin of grapes. A negative Pearson's correlation was found (−0.9110) and this result is consistent with what was expected due to the different principles inherent to these methods.